Proses Peacebuilding di Aceh: dari MoU Helsinki menuju Implementasi Undang-Undang tentang Pemerintahan Aceh - Jemadu, Aleksius (Indonesian Journal of International Law, 2007)
The process of peacemaking in Aceh is based on the acceptance of the peace agreement signed by the Indonesian government and the Free Aceh Movement (GAM) in Helsinki on August 15, 2005. While the signing of the peace agreement were mainly determined by the negotiations between the two sides, the establishment of the Aeh Governance Law is entirely a different political process in the Indonesian parliament. The contestation of political and economic interests among political parties in the deliberative process of the law is inevitable. Thus, the content of the law should be seen as the result of a political compromise. Aceh’s transition from the current negative peace into positive peace will depend on the implementation of this law and the continous transformation of social and economic conditions in Aceh in the post-conflict period. In the final analysis, it is the political elite of Aceh themselves who will determine the success of the peacebuilding.